2007
DOI: 10.1007/s00542-007-0479-x
|View full text |Cite
|
Sign up to set email alerts
|

Squeeze film effects on dynamic performance of MEMS μ-mirrors-consideration of gas rarefaction and surface roughness

Abstract: The squeeze film behavior of MEMS torsion mirrors is modeled, analyzed and discussed. Effects of gas rarefaction (first-order slip-flow model with non-symmetric accommodation coefficients, ACs) and surface roughness are considered simultaneously by using the average Reynolds type equation (ARTE). Based on the operating conditions with small variations in film thickness and pressure, the ARTE is linearized. A coordinate transformation, by stretching or contracting the axes by referring to the roughness flow fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…On the other hand, besides the electrostatic force and geometrical and material specifications, the ambient temperature variations [12][13][14] and squeeze film effects of surrounding gas [15][16][17] could also affect the free vibration and transient responses and instability conditions. When the microstructure is located in a gas medium, the added damping of the gas comes into view in low frequency ranges, while in the high frequency range, the stiffness effects of the surrounding medium become more important [18].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, besides the electrostatic force and geometrical and material specifications, the ambient temperature variations [12][13][14] and squeeze film effects of surrounding gas [15][16][17] could also affect the free vibration and transient responses and instability conditions. When the microstructure is located in a gas medium, the added damping of the gas comes into view in low frequency ranges, while in the high frequency range, the stiffness effects of the surrounding medium become more important [18].…”
Section: Introductionmentioning
confidence: 98%
“…Fukui and Kaneko [5] derived the modified Reynolds equation with Poiseuille flow rate (Q P ) to model the effect of gas rarefaction. Also, the surface roughness effect can be solved by (1) mixed average film thickness functions [6], (2) average flow factors [3,[7][8][9][10] for all surface roughness pattern directions, and (3) using the fractal model [11] to generate functions for random surface roughness. To consider the surface roughness patterns, Patir and Cheng [12] first proposed the modified Reynolds equation using flow factors.…”
Section: Introductionmentioning
confidence: 99%
“…Lee Y-B et al [14] compared the bearing load capacity between the continuous flow model and the rarefied model, and the conclusion indicated that the bearing capacity considering the rarefaction effect was only 90% of that without considering the rarefaction effect. Li WL [15] used the first-order slip-flow model with non-symmetric accommodation coefficients to simulate the rarefaction effect and coupled the surface roughness model with the dynamic analysis of the bearing. His research showed that the decrease of the Kn number enhanced the rarefaction effect.…”
Section: Introductionmentioning
confidence: 99%